Pengembangan LKPD Elektronik Materi Perbandingan Trigonometri Pada Segitiga Siku-Siku Berbasis Etnomatematika - Muhammad Riza; Noor Fajriah; Taufiq Hidayanto (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Online learning was an option during the COVID-19 pandemic, so teachers cannot directly see the activities of their students. Therefore, exciting teaching materials were needed and facilitate independent learning for students. Based on this, an electronic LKPD for trigonometric comparisons in ethnomathematical-based right triangles was developed in the cultural heritage buildings of Banjarmasin City. The purpose of this research was to produce valid LKPD. This study uses the research and development (RnD) method with a 4D model but was carried out only up to three stages: define, design, and develop. The results of material validation based on aspects: format, content, language, and culture were declared valid. Meanwhile, based on media validation, which was seen from the elements: design and ease of operation are also categorized as accurate, so an ethnomathematics-based electronic LKPD was obtained in a valid Banjarmasin City cultural heritage building. Electronic LKPD still needs to be tested on students to be used in the learning process.Keyword: Electronic student worksheets, trigonometric comparisons, ethnomathematics, cultural heritage buildings.